Population differentiation and speciation in the genus Characidium (Characiformes: Crenuchidae): effects of reproductive and chromosomal barriers - Pucci, Marcela Baer; Barbosa, Patricia; Nogaroto, Viviane; Almeida, Mara Cristina; Artoni, Roberto Ferreira; Pansonato-Alves, Jose Carlos [UNESP]; Foresti, Fausto [UNESP]; Moreira-Filho, Orlando; Vicari, Marcelo Ricardo (Wiley-Blackwell, 2014)
Both time and low gene flow are the key factors by which different biological species arise. The divergence process among lineages and the development of pre- or postzygotic isolation occur when gene flow events are lacking. The separation among species of the genus Characidium was analysed in relation to the geomorphological mechanisms in river courses, events of captured adjacent upland drainages in south-eastern Brazil, and sex chromosome differences. The ZZ/ZW sex chromosomes of Characidium vary in size, morphology, degree of heterochromatinization, and presence/absence of ribosomal DNA. The goal of this study was to understand the mechanism of sex chromosome differentiation, its close association with the geological history of cladogenetic events among drainages, and reproductive isolation leading to Characidium speciation. The W-specific probe from Characidium gomesi generated a highlighted signal on the entire W chromosome of C. gomesi, Characidium heirmostigmata, Characidium pterostictum, and Characidium sp., instead of karyotypes of three Characidium aff. zebra populations, which showed scattered signals. An evolutionary and biogeographic landscape arose by analysis of ribosomal DNA site location and differentiation of the sex chromosomes, which established mechanisms of reproductive isolation leading to meiotic barriers, keeping the biological unit distinct even if the contact among species was restored. (c) 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 541-553.
Keywords: whole chromosome painting; cytogenetic; sex chromosomes; karyotypic evolution